Cryopreservation of Sterlet Sperm: Optimization of Cryoprotective Medium Composition - Puhovkin, Anton Yu.; Kononenko, I. S.; Kononenko, R. V.; Butskiy, Kyrylo I.; Cherepnin, V. A.; Kopeika, Eugeniy F. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):160.